Perumusan Masalah Kebijakan, Alternatif Kebijakan, dan Rekomendasi Kebijakan dalam Mempengaruhi Perkembangan Kurikulum Pendidikan - Puji Ambarwati; Nanang Fathurrohman; Anis Fauzi (Jurnal Syntax Admiration, 2024)
The curriculum is a central element in the education system that plays an important role in determining the direction and goals of education. A quality and relevant curriculum is the key to producing young people who are competent and able to answer future challenges. In an ever-evolving global context, the dynamics of change and demands on education systems are increasingly complex. This encourages the need for continuous curriculum adjustment and development. Effective curriculum development cannot be done in isolation from education policy. The right education policy is the foundation for the formulation of a quality and future-oriented curriculum. This study aims to provide input and enrich understanding of the systematics of policy problem formulation, policy alternatives and policy recommendations in influencing the development of the educational curriculum and assisting education stakeholders in the process of developing an educational curriculum. This research is qualitative research using literature study methods or literature research. The formulation of policy problems, policy alternatives, and policy recommendations are three important elements that are interrelated and have a significant influence on policy making. Public policies are detailed so as to be able to find which things are important in making decisions. Education policy is a part of public policy that is closely related and influences each other.